Effect of lime, steel mill slag and phosphorus (P) in absorption of silicon and production of Tanzania grass (Panicum maximum) - Moda, Leandro Rosatto [UNESP]; Prado, Renato de Mello [UNESP]; Puente, Reinaldo José Alvarez; Flores, Rilner Alves; dos Santos, Carlos Leandro Rodrigues; Correia, Marcus André Ribeiro (My University, 2015)
Many pasture areas have Al toxicity, P deficiency and low pH as limiting factors; thus, slag from steel mill can improve Tanzania grass phosphate nutrition by the beneficial effects of the interaction of Si and P. The objectives of this work were to evaluate the availability of P and Si in the soil, growth, P and Si accumulation and dry matter production in Tanzania grass plants. The experiment was carried out in a green house in a low-P soil amended with slag and lime and fertilized with P during three cutting seasons at Jaboticabal - São Paulo, Brazil. The experimental design was a randomized block arranged in a 2×5 factorial with three replicates. Treatments consisted of lime and steel mill slag applications. The other sources of variation were five rates of P [0, 100, 200, 300 and 600 mg dm-3 pot-1 as triple superphosphate (45% of P2O5 soluble in citric acid at 2%)]. The experimental units were 3 dm3 pots. There were increases in the variables plant growth and forage production with increases in available P, suggesting the use of slag as a soil amendment. Slag as soil corrective improved soil chemical attributes by pH correction and by increases in the base saturation index, reflecting in yield gains and in P and Si accumulation in the forage Panicum maximum. However, it did not increase the available Si in the soil, due to the low rates supplied, and did not differ from the traditional source regarding the availability of P in the soil.
Keywords: Acidity corrective; P-resin; Triple superphosphate